Pengaruh Struktur Modal Terhadap Kinerja Keuangan Perusahaan di Sektor Manufaktur - Andri; Nurul Azizah Rahman (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to analyze the impact of capital structure on the financial performance of food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. Additionally, the research investigates the roles of company size and company growth as supplementary independent variables. Employing a quantitative approach with multiple linear regression analysis, this study samples from food and beverage manufacturing companies listed on the IDX during the specified period. Data were collected through a questionnaire using a 5-point Likert scale, measuring capital structure, company size, company growth, and financial performance. The results indicate that capital structure has a significant positive effect on financial performance (β = 0.285, p < 0.05). Company size shows a marginal positive influence (β = 0.318, p < 0.10), while company growth demonstrates no significant effect. The research model explains 27.8% of the variation in financial performance (Adjusted R² = 0.278). These findings underscore the importance of optimizing capital structure in enhancing the financial performance of companies in this sector. Managerial implications include focusing on effective capital structure management while considering the company size factor. This study contributes to the understanding of financial performance determinants in the context of Indonesia's food and beverage industry, while acknowledging the complexity of this phenomenon and the need for further research on other potentially influential factors.